Enhancing the Concentration Capability of Nonsupported Electrically Driven Liquid-Phase Microextraction through Programmable Flow Using an All-In-One 3D-Printed Optosensor: A Proof of Concept - Sahragard, Ali; Carrasco-Correa, Enrique Javier; Cocovi-Solberg, David J; Kubáň, Pavel; Miró, Manuel (Analytical chemistry, 2024)
A versatile millifluidic 3D-printed inverted Y-shaped unit (3D-YSU) was prototyped to ameliorate the concentration capability of nonsupported microelectromembrane extraction (μ-EME), exploiting optosensing detection for real-time monitoring of the enriched acceptor phase (AP). Continuous forward-flow and stop-and-go flow modes of the donor phase (DP) were implemented via an automatic programmable-flow system to disrupt the electrical double layer generated at the DP/organic phase (OP) interface while replenishing the potentially depleted layers of analyte in DP. To further improve the enrichment factor (EF), the organic holding section of the OP/AP channel was bifurcated to increase the interfacial contact area between the DP and the OP. Exploiting the synergistic assets of (i) the continuous forward-flow of DP (1050 μL), (ii) the unique 3D-printed cone-shaped pentagon cross-sectional geometry of the OP/AP channel, (iii) the bifurcation of the OP that creates an inverted Y-shape configuration, and (iv) the in situ optosensing of the AP, a ca. 24 EF was obtained for a 20 min extraction using methylene blue (MB) as a model analyte. The 3D-YSU was leveraged for the unsupervised μ-EME and the determination of MB in textile dye and urban wastewater samples, with relative recoveries ≥88%. This is the first work toward analyte preconcentration in μ-EME with in situ optosensing of the resulting extracts using 3D-printed millifluidic platforms.